Voiding cystourethrogram in the diagnosis of vesicoureteric reflux in children with antenatally diagnosed hydronephrosis - R B Nerli; S S Amarkhed; I R Ravish (Dove Medical Press, 2008)
R B Nerli, S S Amarkhed, I R RavishDepartment of Urology, Kles Kidney Foundation, Nehru Nagar, Belgaum, IndiaAbstract: Prenatal ultrasonography has revolutionized the detection and management of many urological abnormalities. Vesicoureteric reflux (VUR) which develops in 10% to 15% of cases of prenatal hydronephrosis, is difficult to predict prenatally. While all children with prenatal hydronephrosis should undergo ultrasonography within the first few weeks of life, there seems to be controversy regarding the role of voiding cystourethrogram (VCUG) in the assessment of these children.Materials and methods: Neonates with antenatally diagnosed unilateral hydronephrosis were prospectively assessed with sonography on day 3–7, and VCUG and isotope imaging at three months.Results: Seven (16.6%) children of the 42 children with Society of Fetal Urology grade 0/I/II hydronephrosis on postnatal sonography had evidence of VUR on VCUG. 44.4% of the refluxing ureters identified involved high grade disease and two (28.5%) children required reimplantation.Conclusions: Children with fetal reflux may be diagnosed prior to urinary tract infection and in whom further renal injury may be prevented. VCUG when performed properly is safe and presents with little risk of infectious and noninfectious complications. VCUG should be done in children in whom hydronephrosis is detected prenatally to restrict the use of VCUG to diagnose VUR. Two patients had infection.Keywords: antenatal hydronephrosis, voiding cystourethrogram, vesicoureteric reflux